Study of bone marrow iron storage in patients presented with pancytopenia - Padmakar Bardapurkar; Ruchi Samir Randive; Sushama Gurwale; Charusheela Rajesh Gore; Vidya Viswanathan (Journal of the Scientific Society, 2023)
Introduction: Bone marrow examination is a useful technique for the evaluation of both hematological and nonhematological diseases. Perls Prussian blue stain is the “gold standard” to demonstrate the iron content and hemosiderin in the sideroblasts and the bone marrow macrophages. In our study, we assess the grades of iron storage in the bone marrow, as seen in various diseases in pancytopenia patients. Materials and Methods: An evaluation of iron storage in bone marrow aspirate of 140 patients of pancytopenia in a tertiary care center in western India, using Perls' stain and Gales' system of grading. Results: Out of all pancytopenia cases, 60.71% of the cases had low iron stores, 30% had normal, and 9.29% of cases had high iron stores, using Gales' system of iron stores grading. Dimorphic anemia was in the range of 0–3 iron store grade, with 72.4% having low iron stores, 24.6% having normal iron stores, and 2.8% having high iron stores. Megaloblastic anemia showed iron store grade in the range of 0–4, and iron-deficiency anemia showed decreased iron stores, along with multiple myeloma, acute lymphoblastic leukemia, and aplastic anemia. Conclusion: Gale's method of grading is used universally to grade iron stores in bone marrow aspirate as it is highly convenient and result oriented and it helps clinicians to plan necessary treatment accordingly.